Social Conflict Resolution and Collective Action in Contemporary Multicultural Societies - Fazsya Tatra Khalia; Melva Noya; Edyanto Edyanto; Maudhy Satyadharma; Deford Cristy Birahy (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study investigates how social conflict resolution practices interact with collective action dynamics in contemporary multicultural societies through an empirical mixed-methods design integrating survey modeling, interviews, and observational analysis. Quantitative findings reveal that perceived procedural fairness, identity negotiation competence, and institutional transparency significantly predict intergroup trust, collective efficacy, and sustained participation. Qualitative evidence demonstrates that dialogical mediation reframes conflict as a cooperative learning process, enabling participants to transform identity tension into shared civic engagement. The analysis identifies a recursive architecture in which culturally responsive conflict mechanisms, recognition-based identity framing, and adaptive institutional structures jointly stabilize collective cooperation. Structural models show that emotional regulation and legitimacy perceptions mediate the transition from disagreement to coordinated action, while narrative data illustrate how culturally grounded practices enhance resilience and participation continuity. The integrated interpretation positions conflict not as social breakdown but as a generative site of institutional learning and identity recalibration. The study contributes a multi-level framework explaining how multicultural societies sustain cooperation by embedding fairness, recognition, and reflexive governance into everyday conflict engagement.